First record of Hylaeus (Gnathoprosopis) euxanthus (Hymenoptera: Colletidae) in Chile - Montalva, Jose Miguel; Dudley, Leah S.; Houston, Terry F. (Journal of Melittology, 2019)
A 2009 field survey at Cerro San Cristobal, Santiago, Chile, revealed the presence of Hylaeus (Gnathoprosopis) euxanthus (Cockerell, 1910). Since then, numerous individuals have been observed visiting several plant species around Santiago and Valparaíso. This is the first record of this Australian-native bee in South America.